PENGARUH AKTIVITAS OUTDOOR EDUCATION TERHADAP SOCIAL SKILLS DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Gunawan, Asep Sahrul; Andi Bagja Munggaran; Ananda Adiputra Pratama; Pramudya Ade Wiguna; R. Alpin Wirayuda (KAMPUS AKADEMIK PUBLISING, 2026)
This study was motivated by the low social skills of MTS Al-Hidayah students. One of the efforts to improve social skills in this study is by implementing outdoor education activities. One of the main objectives of this outdoor activity is to involve students in productive activities, because through sports and recreational activities, it can contribute to the development of social, emotional, and behavioral skills. This study aims to determine the effect of outdoor education activities on social skills in MTS Al-Hidayah students. The study was conducted using a quantitative approach with a pre-experimental type and one group pretest posttest design on 24 grade VII MTS Al-Hidayah students with a sampling technique using cluster sampling. Data related to social skills in this study were collected using a non-test instrument, namely a social skills questionnaire. The results of data analysis using the two-mean difference test on the social skills variable found a difference in the mean in the pretest and posttest by obtaining a sig. (2-tailed) value of 0.00 <0.05, meaning Ho is rejected so that it can be concluded that there is a significant effect of outdoor education activities on social skills in MTS Al-Hidayah students.